A Novel Use of Buccal Fat Pad Flap for Immediate Reconstruction of Palatal Tumor Resection Defect. Issue 7 (October 2019) - Koç, Onur; Tüz, Hakan H.; Tosun, Emre
Abstract : Abstract: Integrity of the palatal mucosa may be disrupted due to various pathological and congenital factors. In maxillofacial defects, the buccal fat pad has been used frequently to repair the palatal region and close oro-nasal communications. In this case report, the use of buccal fat pad for the closure of a surgical palatal defect is presented with a 3-year follow-up. A 75-year-old female patient visited our clinic with a complaint of a non-adaptive maxillary denture. During clinical and radiographic examination, a well-demarcated mass on the palatal mucosa extending to the soft palate of the left side was observed. Subsequent to resection of the tumor, a defect occurred on the palatal region extending toward the soft palate. The pedicled buccal fat pad was chosen for closure of the defect. The patient was followed-up at 3, 7, 14, and 30 days after surgery. Epithelization and healing of the surgical wound were uneventful. At the 3-year follow-up, functional closure of the left palatal region was observed with no recurrence. Buccal fat pad is an easily manipulated flap with predictable results for the reconstruction of medium-sized defects of the oral and maxillofacial region with minimal postoperative discomfort for the patient.